2012
DOI: 10.1177/1069397112450859
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Cultural Investigation of Compliance Without Pressure

Abstract: Compliance-without-pressure techniques have been widely studied in North America and West Europe. Among these techniques, the "but you are free" (BYAF) is a verbal compliance procedure that solicits someone to comply with a request by simply telling a person that he or she is free to accept or refuse the request. This technique is interpreted with the commitment theory and the psychological reactance theory which are more relevant in individualistic cultures than in collectivist cultures. So, four studies

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
1
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 48 publications
1
13
1
1
Order By: Relevance
“…Yet, there were no differences in state or trait reactance between European Canadians and East Asian Canadians. These findings, on the surface, seem to be at odds with some previous research which suggests a link between independent self-construal and psychological reactance (e.g., Savani et al 2008;Pascual et al 2012).…”
Section: Discussioncontrasting
confidence: 93%
See 1 more Smart Citation
“…Yet, there were no differences in state or trait reactance between European Canadians and East Asian Canadians. These findings, on the surface, seem to be at odds with some previous research which suggests a link between independent self-construal and psychological reactance (e.g., Savani et al 2008;Pascual et al 2012).…”
Section: Discussioncontrasting
confidence: 93%
“…We included two cultural groups to which to compare the Iranian cultural grouppeople from European and East Asian cultural backgrounds. Consistent with the literature (e.g., Jonas et al 2009;Pascual et al 2012), we expected that individuals from European North American (vs. East Asian) cultural backgrounds would exhibit a higher degree of psychological reactance because of higher level of independent self-construal. Taken together, we expected that participants from an Iranian cultural background would exhibit more psychological reactance than would participants from European cultural backgrounds, who in turn would exhibit more psychological reactance than would participants from East Asian cultural backgrounds.…”
Section: The Present Studysupporting
confidence: 75%
“…This study was controversial, and the subject of numerous replications (Quiamzade and Mugny, 2009) and reviews (see Blass, 2004). The effect appears to be robust across cultures (Pascual et al, 2012).…”
Section: Personal Influencementioning
confidence: 92%
“…Although the transculturality of social infl uence processes is a fi eld of Unauthenticated Download Date | 5/12/18 12:58 PM research that has been litt le investigated by social psychologists, several studies (Aaker, 2000;Cialdini, Wosinska, Barrett , Butner, & Gornik-Durose, 1999;Han & Shavitt , 1994) have nevertheless demonstrated that the eff ects of persuasive communications varied in diff erent cultures (Courbet & Marchioli, in press). In a similar vein, persuasion techniques like the touch technique (Kleinke, 1977) and the "but you are free of" technique (Guéguen & Pascual, 2000), or those based on successive requests as with the foot-in-the-door technique (Freedman & Fraser, 1966), are also known for being sensitive to cultural eff ects (Guéguen & Pascual, 2000;Pascual et al, 2012;Petrova, Cialdini, & Sills, 2007). In the light of these theoretical elements, the disrupt phase can be interpreted, on the one hand, as the disruption of a communication situation by an odd element, an element that could not have been predicted by the subjects and which alters the sequence of events initially expected in accordance with the social situation activated.…”
Section: A Technique Both Contextual and Cultural In Naturementioning
confidence: 99%
“…cross-cultural (Pascual & Guéguen, 2004; see also Pascual et al, 2012). According to Morling and Lamoreaux (2008), messages in a persuasive paradigm "can also induce intuitively 'opposite' eff ects" depending on the culture (Aaker & Williams, 1998).…”
mentioning
confidence: 99%